Sur les ailes du vautour. Genre, violence et « résistance » dans un récit nahua de voyage à Chiknâujtipan, le monde des morts (Mexique) - Dominique Raby (Journal de la Société des Américanistes)
On the wings of the vulture : gender, violence, and « resistance » in a Nahua tale of a trip to Chiknâujtipan, the land of the dead (Mexico). This essay analyzes four versions of a contemporary Nahua Orpheus tale (Mexico), inherited from a pre-Hispanic myth and colonial exempla, to underline how the intersection of gender and economic occupation influences the message and morality given to the tale by the storytellers. The author examines how female storytellers use a number of techniques and spaces of creativity to question certain male behaviors, while promoting fundamental Nahua values. These particularities allow for recontextualizing the « traditional resistance » and social change dichotomy, in the context of indigenous Latin America.